Safeguarding patient safety: A need to re-examine the legal responsibilities of medical trainees - Mohd Zaini, Nur Farha; Jahn Kassim, Puteri Nemie (Universitas Muhammadiyyah Yogyakarta, 2017)
Although possessing the basic skills of practicing medicine, the post of ‘medical trainees’ are considered to be transitory until they metamorphose into fully qualified medical doctors. Thus, the medical training period tends to be crucial as it serves as a platform for the trainees to gain all the required practical knowledge and skills in treating the patients. During this period, medical trainees may be vulnerable to risks of medical errors, particularly, if they are not well supervised and are subjected to perform tasks that are beyond their capability. Many other factors such as heavy workload, fatigue and carelessness could lead to preventable medical errors causing patient safety to become compromised. Medical trainees may also find themselves exposed to law suits although the potential of being individually liable would be rare due to their status which is still considered as equivalent to ‘students’ under training. Nevertheless, the implications of medical errors may lead to patients’ suffering physical injuries and also death in which their supervisors and hospitals may be held vicariously liable for their actions in the court of law. Subsequently, legal and judicial intervention have thus, become more prevalent in cases involving medical trainees as courts in various jurisdictions such as the United States, Canada and England have imposed high standard of care to be adhered to by medical trainees. Therefore, in safeguarding patient safety, it is imperative that medical trainees strive to attain the highest professionalism at all times in respecting the goals of patient safety and the demands of legal standards.